Editorial: From judge to jury: the potential for crowd reviewing. Issue 2 (March 2022) - Akın Ateş, Melek; Luzzini, Davide; Meehan, Joanne; Suurmond, Robert
Abstract: In this editorial, we introduce the four best papers selected from the IPSERA 2021 conference for this special issue of the Journal. We discuss how a double-blind crowd review (CR) process was used as an alternative to the traditional "two reviewer" double-blind peer review system. After a brief review of the literature and the existing debate around academic peer review, we introduce the main characteristics of CR. Next, at the core of our discussion, we report on the results of a pilot CR project that we conducted to review JPSM articles associated with the 2021 IPSERA Conference. We describe in detail the review process, and we illustrate the feedback received from reviewers and authors on the CR process, as well as our perspective as guest editors. Finally, we draw some conclusions and present recommendations for CR in the Purchasing and Supply Management (PSM) field. The CR pilot contributes to the wider debate around peer-reviewing by offering insights into the experience of different stakeholders and by highlighting the benefits and pitfalls of CR.